Rohc-Mpls Tunnel Architecture For Wireless Mesh - Sarwar, Muhammad Imran (2018)
Natural or human-made disasters are sudden events that can cause significant damage, especially to the network communication infrastructure. In these events, a rapid deployment of network communication systems is required in order to relay or receive the communication among the people in the disaster areas to conduct relief and rescue efforts. Wireless mesh networks have emerged and has been recognised for its potential for rapid deployment and last mile coverage of network infrastructure, which is highly suitable for emergency response management. While wireless mesh networks have beneficial attributes, it also introduces some crucial problems. During data transmission, the path recovery time is significantly higher resulting in the loss of data if node and link failures occur.